At the “Crux” of Henryk Gorecki’s Totus Tuus, Op. 60: Signification of Polish Catholic Marian Devotion - Helmcke, William M. (Interdisciplinary Studies in Musicology, 2018)
Henryk Górecki was a devout Polish Catholic composer. He testified that many of his compositions refer to Bogurodzica, a medieval Polish hymn pertaining to Marian devotion. Furthermore, Górecki himself wrote the first seven notes of Bogurodzica on a compositional sketch. This act strongly indicates that the first seven notes of Bogurodzica signify its sum. Consequently, the article has argued that Górecki derived three motives from the first seven notes of Bogurodzica and transformed them into musical signifiers of signified Polish Catholic Marian devotion in Totus Tuus. These motives include a descending fourth derived from Bogurodzica notes 3-6; a verticalization of the fourth; incomplete neighbor from Bogurodzica notes 1-2 and complete neighbor from Bogurodzica notes 5-7; and a voice exchange that visually depicts the Christian Cross as Augenmusik. The Bogurodzica-basei motives thoroughly saturate the crux of the composition. Within the sacred pitch space of Totus Tuus Górecki, the high priest of Holy Minimalism, delivers a profoundly moving autobiographical homily preaching the musical signification of Marian devotion.